Fear of childbirth: validation of the Kiswahili version of Wijma delivery expectancy/experience questionnaire versions A and B in Tanzania - Agnes F. Massae; Margareta Larsson; Sebalda Leshabari; Columba Mbekenga; Andrea B. Pembe; Agneta S. Svanberg (BMC, 2022)
Abstract Background Fear of childbirth is common both before and after childbirth, often leading to complications in mother and new-born. The Wijma Delivery Expectancy/Experience Questionnaires (W-DEQ) are commonly used to measure fear of childbirth among women before (version A) and after childbirth (version B). The tools are not yet validated in the Tanzanian context. This study aimed to validate the reliability, validity, and factorial structure of their Kiswahili translations. Methods A longitudinal study was conducted in six public health facilities in the Pwani region, Tanzania. In all, 694 pregnant and 625 postnatal women were concurrently selected and responded to W-DEQ-A and W-DEQ-B. Validation involved: translating the English questionnaires into Kiswahili; expert rating of the relevancy of the Kiswahili versions' items; computing content validity ratio; piloting the tools; data collection; statistical analysis with reliability evaluated using Cronbach's alpha and the intraclass correlation coefficient. Tool validity was assessed using factor analysis, convergent and discriminant validity. Exploratory factor analysis and confirmatory factor analysis were conducted on data collected using W-DEQ-A and W-DEQ-B, respectively. Results Exploratory factor analysis revealed seven factors contributing to 50% of the total variation. Four items did not load to any factor and were deleted. The factors identified were: fear; lack of self-efficacy; lack of positive anticipation; isolation; concerns for the baby; negative emotions; lack of positive behaviour. The factors correlated differently with each other and with the total scores. Both Kiswahili versions with 33 items had good internal consistency, with Cronbach's alphas of .83 and .85, respectively. The concerns for the baby factor showed both convergent and discriminant validity. The other six factors showed some problems with convergent validity. The final model from the confirmatory factor analysis yielded 29 items with good psychometric properties (χ2/df = 2.26, p =  < .001, RMSEA = .045, CFI = .90 and TLI = .81). Conclusions The Kiswahili W-DEQ-A-Revised and W-DEQ-B-Revised are reliable tools and measure fear of childbirth with a multifactorial structure, encompassing seven factors with 29 items. They are recommended for measuring fear of childbirth among pregnant and postnatal Tanzanian women. Further studies are needed to address the inconsistent convergent validity in the revised versions and assess the psychometric properties of W-DEQ-A among pregnant women across gestational ages.